Exploration and Practice of Pressure Relief by Slotting Coal Seams with a Diamond Wire Saw - Zhu Tang; Shuqing Li; Fei Huang; Shouqing Huang; Kangxu Cai (Advances in Civil Engineering)
To safely and economically eliminate the threat of high geostress in the coal mining process, based on the engineering case study of pressure relief by slotting residual coal pillars at a mine in the Kailuan mining area, a method of pressure relief by slotting coal seams with a wire saw was explored, and numerical simulation was carried out. The results show that the wire saw can cut coal seams in a large area, with a cutting efficiency and slotting depth greater than those of hydraulic slotting; a stress concentration zone forms in front of the wire saw coal cutting working face and a stress reduction zone and a stress recovery zone form behind. The pressure relief range varies, increasing at first and then decreasing. The exploration and practice of pressure relief by slotting coal seams with a diamond wire provides theoretical guidance and practical reference for pressure relief by slotting coal seams.